Failure modes in GFRP composites assessed with the aid of SEM fractographs. (2021) - Beura, S.; Chakraverty, A.P.; Thatoi, D.N.; Mohanty, U.K.; Mohapatra, M.
Abstract: Hand-laid, 18 layered, E-Glass/Epoxy resin (GFRP) composite specimens were exposed to distilled water immersion at 65 °C (hydrothermal conditioning), a moist ambience with 95% relative humidity at 60 °C (hygrothermal conditioning) and sea water immersion (at room temperature) for different lengths of time. The treated samples were then exposed to both up and down thermal shocks. The specimens were also exposed to gamma irradiations pertaining to both high and low intensity gamma doses. Three-point Bend test of the samples so treated, was carried out in a universal testing machine and the failure modes as revealed from the SEM fractographs of the fractured specimens surfaces subjected to SEM analysis were recorded and analyzed. The samples conditioned differently for different lengths of time exhibited different extents of structural damages and adopted different modes for the ultimate failure. Any one or any combination of failure modes such as matrix-cracking, fibre pull-out, fibre–matrix de-bonding etc. indicating the interfacial failure were seen to be the chief mode of failure/disintegration of the GFRP composite specimens.